If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 3a + -5a + -1a + 7 Reorder the terms: 7 = 7 + 3a + -5a + -1a Combine like terms: 3a + -5a = -2a 7 = 7 + -2a + -1a Combine like terms: -2a + -1a = -3a 7 = 7 + -3a Add '-7' to each side of the equation. 7 + -7 = 7 + -7 + -3a Combine like terms: 7 + -7 = 0 0 = 7 + -7 + -3a Combine like terms: 7 + -7 = 0 0 = 0 + -3a 0 = -3a Solving 0 = -3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '3a' to each side of the equation. 0 + 3a = -3a + 3a Remove the zero: 3a = -3a + 3a Combine like terms: -3a + 3a = 0 3a = 0 Divide each side by '3'. a = 0 Simplifying a = 0
| x/3-1= | | .7x=25000 | | 4(3x-5)=-50 | | 21s^2+43s+20=0 | | -0.51x-3.2=0.8+7.28 | | 1.15g+1.25g=15 | | 25y^2+49y-4=0 | | -7x+2y=-51 | | 18.5w+6.5w-2.8w=149.1 | | 3x-21x=0 | | 9-7y=2 | | 90x-5.4=391.4-38x | | 4n-2+7n=29 | | 5x+32=4+2x | | 4+14x^2-7x=0 | | 6b+6=-48 | | -7+8n=5+13n | | 10-1235=21 | | -21x^2-20x-4=0 | | 2x^3-50x+72=0 | | 2+2+1+1+7+3+2+4+1+4= | | 4(x-1)=1.2(x-8) | | 9+10x=.4 | | x^3+x^2-18x-54=0 | | 9+10x=.2 | | 10-29v+10v^2=0 | | 10-1+4+(-16)= | | -9.2-x=4.5 | | 10z+4=2(5z+8) | | -18=-4y+6+2y | | -5(2-3x)=2(4x+1) | | 4b^3+9b^2+5b=0 |